The Effect of Ethanol Extract of Mobe Leaves (Artocarpus lacucha Buch-Ham.) on Caspase-3 Expression in Liver Tissue Rats Induced by Carbon Tetrachloride: English - Lubis, Meiva Amelia; Indah Pertiwi; Damayanti (CV. ARGA FARMA, 2025)
Carbon tetrachloride (CCl₄) is a commonly used hepatotoxic agent to induce liver injury via oxidative stress and the activation of hepatocyte apoptosis. One hallmark of apoptosis is the increased expression of Caspase-3, a key executor enzyme in the programmed cell death pathway. The ethanol extract of Mobe leaves (Artocarpus lacucha Buch-Ham.) is known to contain bioactive compounds such as flavonoids and triterpenoids, which have demonstrated hepatoprotective potential. This study investigates the hepatoprotective effects of ethanol extract of Mobe leaves (EEML) on Caspase-3 expression in the liver tissues of rats induced by carbon tetrachloride. This experimental study utilized 30 male rats randomly assigned into six groups. The negative control group received CCl₄ - and CMC-Na 1%, while the positive control group received silymarin and CCl₄. Four treatment groups received oral doses of EEML at 50, 100, 200, and 400 mg/kg body weight for 15 days with CCl₄ induction. Caspase-3 expression in liver tissue was analyzed using the immunohistochemistry (IHC) method and quantified based on the number of positively stained cells across five microscopic fields. The results showed a significant reduction in Caspase-3 expression (p<0.05) in the EEML-treated groups compared to the negative control, with the 400 mg/kg dose achieving an effect comparable to silymarin. These findings suggest that EEML possesses hepatoprotective properties through apoptosis inhibition, evidenced by decreased Caspase-3 expression in CCl₄ injured liver tissue.